Reversibility of liver fibrosis - Prakash Ramachandran; John P. Iredale (Annals of Hepatology, 2009)
Liver cirrhosis is a major cause of morbidity and mortality worldwide and has very limited therapeutic options. Regardless of the aetiology, hepatic fibrosis is a characteristic feature of chronic liver disease. Our knowledge regarding the pathogenesis of this scarring has grown exponentially in the past 2S years. It has now clear that this is a highly dynamic process and the long-held dogma that it is irreversible and relentlessly progressive is now being challenged. In this review, we will summarise the key pathogenic mechanisms at play and will focus on the evidence demonstrating that liver fibrosis is reversible in humans and animal models. In particular, we will examine the role of hepatic stellate cells, MMPs, TIMPs and macrophages in this process. Finally, we will discuss some of the studies aimed to therapeutically target the resolution of fibrosis and their potential for translation into a badly-needed treatment modality in the clinical setting.